MODERN PROBLEMS OF ENGINEERING EDUCATION: THE RESULTS OF INTERNATIONAL CONFERENCES AND SCIENTIFIC SCHOOL - Vasily G. Ivanov; Vladimir V. Kondratyev; Alla A. Kaybiyainen (Высшее образование в России)
The paper analyzes the proceedings of the 42nd IGIP International Conference onEngineering Pedagogy “Global Challenges in Engineering Education”, 16th ICL conferenceand International scientific school “Engineering education for a new industrialization (plenary sessions reports, learning seminars, subject specific seminars, and experts’ seminars ). Conclusive recommendations of the International scientific school formulated by the conference participants for the authorities and expert community, for the Ministry of education and Science of the Russian Federation, for the representatives of scientific organizations, business structures, engineering companies, and industrial enterprises, for university administration are adduced in the article.